A Framework for Quality of Life Assessment of Urban Green Areas in Europe; An application to District Park Reudnitz Leipzig - Eveline van Leeuwen; Caroline Rodenburg; Ron Vreeker (European Regional Science Association (ERSA), 2003)
A general concern on quality of life, with a particular view to the city has emerged in the last decade. The positive relation between quality of life and urban green is often described as significant. Therefore, public and private decision-makers want and need better information about the quantity and quality of urban green available in their city. Another important aspect to urban green is to which extent the area satisfies the needs of the users and the inhabitants of the city. Only if users are satisfied with the urban green it will increase the quality of life in the city. This paper is part of the project ?Development of Urban Green Spaces to Improve the Quality of Life in Cities and Urban Regions' (URGE). The aim of the URGE project is to improve the provision of cities with green spaces, both qualitatively and quantitatively, thus enhancing the quality of life of the urban population and contributing to the sustainable development of European cities. One major objective is to increase the available knowledge about the complex interactions between nature, economy and social systems in urban environments. To be able to increase this knowledge, several criteria concerning ecological, economic, social and planning attributes have been developed. The purpose of this paper is to describe and discuss an evaluation framework, which can be used to evaluate the quality of an urban green area with help of the developed criteria. This evaluation framework includes Regime Analysis, which is a discrete multi-assessment method suitable to assess projects as well as policies. It can be used to evaluate and compare an urban green area with a benchmark or with other green areas. This paper will describe the evaluation of the Leipzig ?District Park Reudnitz? with help of a benchmark which is composed of planning objectives and expert meanings.
Keywords: 330